PATENT CANCELLATION AS AN EFFORT TO PROTECT PATENTS REGISTERED IN INTELLECTUAL PROPERTY RIGHTS - Teuku Daudsyah; Muhammad Ridwan Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Patents give the owner exclusive rights in an effort to prevent or stop other parties from making, using, offering for sale, selling or importing a product or a process, based on a patented invention, without the permission of the patent owner. Patents are a